2022
DOI: 10.1136/rmdopen-2022-002359
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review informing the consensus statement on efficacy and safety of pharmacological treatment with interleukin-6 pathway inhibition with biological DMARDs in immune-mediated inflammatory diseases

Abstract: ObjectivesInforming an international task force updating the consensus statement on efficacy and safety of biological disease-modifying antirheumatic drugs (bDMARDs) selectively targeting interleukin-6 (IL-6) pathway in the context of immune-mediated inflammatory diseases.MethodsA systematic literature research of all publications on IL-6 axis inhibition with bDMARDs published between January 2012 and December 2020 was performed using MEDLINE, EMBASE and Cochrane CENTRAL databases. Efficacy and safety outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 179 publications
(384 reference statements)
1
5
0
1
Order By: Relevance
“…8 In this respect, whereas several preclinical works demonstrated the key role of IL-6 in the pathophysiology of several connective tissue disease, and early studies reported encouraging results with IL-6 inhibitors in these conditions, targeting IL-6-mediated signaling in SLE myositis and primary Sjögren syndrome did not show superiority in clinical responses versus placebo, except for a potentially beneficial effect of tocilizumab on preservation of lung function in systemic sclerosis-associated interstitial lung disease. 9 In the same way, a failure of tocilizumab was also observed in 2 and 8 patients who received this drug in our series of rhupus and RA/systemic sclerosis overlap syndrome, respectively. 5,10 Thus, until sets of biomarkers associated with particular involvement or predictive of treatment response become available, rather than trying to attribute all the manifestations, including EA, to the same disease, it is preferable, in our opinion, to consider overlapping syndromes as real entities for which it is more relevant to propose therapies having shown their effectiveness in both components of the syndrome.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…8 In this respect, whereas several preclinical works demonstrated the key role of IL-6 in the pathophysiology of several connective tissue disease, and early studies reported encouraging results with IL-6 inhibitors in these conditions, targeting IL-6-mediated signaling in SLE myositis and primary Sjögren syndrome did not show superiority in clinical responses versus placebo, except for a potentially beneficial effect of tocilizumab on preservation of lung function in systemic sclerosis-associated interstitial lung disease. 9 In the same way, a failure of tocilizumab was also observed in 2 and 8 patients who received this drug in our series of rhupus and RA/systemic sclerosis overlap syndrome, respectively. 5,10 Thus, until sets of biomarkers associated with particular involvement or predictive of treatment response become available, rather than trying to attribute all the manifestations, including EA, to the same disease, it is preferable, in our opinion, to consider overlapping syndromes as real entities for which it is more relevant to propose therapies having shown their effectiveness in both components of the syndrome.…”
supporting
confidence: 66%
“…However, the detection of higher levels of interleukin 6 (IL-6) in the blood of SLE patients with JA does not necessarily mean that IL-6 inhibition will be effective 8 . In this respect, whereas several preclinical works demonstrated the key role of IL-6 in the pathophysiology of several connective tissue disease, and early studies reported encouraging results with IL-6 inhibitors in these conditions, targeting IL-6–mediated signaling in SLE myositis and primary Sjögren syndrome did not show superiority in clinical responses versus placebo, except for a potentially beneficial effect of tocilizumab on preservation of lung function in systemic sclerosis–associated interstitial lung disease 9 . In the same way, a failure of tocilizumab was also observed in 2 and 8 patients who received this drug in our series of rhupus and RA/systemic sclerosis overlap syndrome, respectively 5,10 .…”
mentioning
confidence: 99%
“…It has been demonstrated to be effective in treating a wide range of inflammatory diseases, particularly musculoskeletal conditions such as rheumatoid arthritis (RA), osteoarthritis (OA), and tendinitis [58,59]. New information, particularly regarding RA, enabled us to improve treatment strategies involving tocilizumab and other agents [60]. A number of new compounds, including olokizumab and sirukumab, that target both the IL-6R and the IL-6 ligands have been shown to be clinically effective in treating rheumatoid arthritis (RA), according to a number of very significant new findings [32].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the phase III clinical trials involving tocilizumab and sarilumab have not yet been made public and are therefore unclear. This is due to the significant risk of bias that was present in both studies, as well as the absence of a comparator arm in one of the reports [60]. According to research that was conducted and published by Zhang et al in 2020, tocilizumab has the potential to be proposed as an additional medication that is both safe and effective for the prevention of relapses in patients who have neuromyelitis optica spectrum disease (NMOSD).…”
Section: Discussionmentioning
confidence: 99%
“…Особый интерес представляет эффективность монотерапии ОКЗ. Известно, что у пациентов, которым не подходит комбинированная терапия ГИБП и БПВП, иИЛ-6 имеют определенные преимущества в качестве монотерапии перед иФНО-α [31]. В то же время до сих пор исследований ОКЗ в режиме монотерапии не проводились.…”
Section: Discussionunclassified